Interculturality and Internationalization in the design of the subjects of Introduction to Systems Engineering and Computing and Introduction to Industrial Engineering at Universidad Nacional de Colombia (LACCEI, 2024)
This document describes the Transformation of the Subjects of Introduction to Systems and Computing Engineering, and Introduction to Industrial Engineering at Universidad Nacional de Colombia. This is in order to achieve the Interculturality and internationalization of curriculum. This transformation is supported by the Internationalization Model of the Curriculum in four levels. It states the national guidelines regarding the accreditation and internationalization of higher education in Colombia. It exposes the eight challenges that the subjects face for their Interculturality and Internationalization of the Curriculum, the foundations of Interculturality, the model and the design of the Subjects under these approaches. The design of the Internationalized Subjects implies: the definition of expected learning results, the presentation of innovative teaching-learning methodology, as well as the specification of teaching and learning strategies, and the methodology for authentic assessment and evaluation, which is designed in coherence and with respect to the achievement of the Intended Learning Outcomes of the students.